ANALISIS DAMPAK PATRON CLIENT TERHADAP PENDAPATAN PETANI SAGU DI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI - Zuriyadi, Fahmi; Hendro, Ekwarso; Taryono, Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to determine the Patron Client system of sago farmers' income in Merbau District, Meranti Islands Regency The population of this research was 89 people who did patron client to sago farmers, and the sample was taken using the census sample method, that is, all the people who carried out the patron client were sampled. The type of data used were primary data and secondary data. Data collection techniques using interview techniques, questionnaire techniques, and documentation techniques. The analytical method used in this research is descriptive and quantitative using income formulas The results of this study illustrate the Patron Client System of Sago Farmers' Revenue in Merbau District, Kepulauan Meranti Regency. difference from Production Sectors. and the second system of Harvesting of this system is also different in each Toke in receiving purchases of crops by the owner of the sago plantation land, there are those who buy by way of the Petitioners and there are also Pertuals, with details of the costs purchased by each Toke vary. Based on the Patron Client, the income between the Sago Farmers and Toke Land Owners can be concluded that the size of the Land Ownership and Toke Income is in accordance with the size of the dependents of each Land Owner in his Toke Land. The dependents issued by the Land Owner are greater than the Toke dependents, so that the Income obtained by the Land Owner is smaller than the Toke income in Merbau Subdistrict, Kepulauan Meranti Regency.Keyword: Patron Client System, Sago Patani Revenue